The Effect of Future Planning Information Services on Career Choices For Class XI Ipa1 SMAN 4 Palu - Nurtang Nurtang; Durrotunnisa Durrotunnisa (Education Journal, 2020)
The purpose of this study was to examine the effect of future planning information services on career choices, so that students are able to plan their careers optimally according to their potential. This study used a one group design research design. The data collection technique used a questionnaire, so the sample amounted to 29 people, namely students of class XI Ipa 1. Data analysis techniques obtained t-count greater than t-table (4,56>1,70). So Ha is accepted and H0 is rejected. The hypothesis which, states “there is a significant difference between career choices before and after being provided with future planning information services”. So it can be concluded that there is an effect of providing future planning information services on the career choices of class XI Ipa 1 students.